1953
DOI: 10.1039/df9531400089
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of lead tetraethyl as an inhibitor of combustion processes

Abstract: Older theories of action of lead tetraethyl are briefly discussed. New experiments are summarized, showing (i) lead tetraethyl, on oxidation, first forms PbO as a colloidal fog, (ii) lead tetraethyl almost certainly inhibits by virtue of forming PbO, (iii) PbO is an inhibitor because it causes a surface destruction of chains. A simple way is described of coating a quartz reaction vessel with a thin film of PbO. Such a vessel is then used for the study of the effect of PbO on particular combustion reactions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1960
1960
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…From indirect evidence LValsh and co-urorliers have suggested that the radical HOz plays such a role in the oxidation of methane a t about 500" C (20,22). In the oxidation of higher paraffins a t low temperatures, many other radicals have been postulated as participating in the reaction mechanism (10,27,32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From indirect evidence LValsh and co-urorliers have suggested that the radical HOz plays such a role in the oxidation of methane a t about 500" C (20,22). In the oxidation of higher paraffins a t low temperatures, many other radicals have been postulated as participating in the reaction mechanism (10,27,32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the chemical trallsformatioll is liltely to release ethyl radicals into the combustion mixture and so cause solne promoting action. An explanation is then available for the observation that lead tetraethyl has a net promoting effect ~lllder certain esperilnental conditions, for example, a t very high temperatures (17) or with fuels that are believed to oxidize via very short chains (10,20).…”
Section: Relation To the Mechanism Of Antiknock Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…For personal use only. [22] .H + CHzCO = Hz + C H C O La terminaison des chaines, compte-tenu des effets de surface observCs, est sans doute hCtCrogene et, parmi les radicaux, HO, est le plus susceptible de se detruire sur la paroi, en particulier recouverte de chlorure de potassium ou d'oxyde de plomb (21).…”
Section: Mcthode Expkrimentale ( a ) Appareillageunclassified